2021
DOI: 10.1155/2021/6659240
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Puerarin Attenuates LPS‐Induced Inflammatory Responses and Oxidative Stress Injury in Human Umbilical Vein Endothelial Cells through Mitochondrial Quality Control

Abstract: Atherosclerosis is closely associated with the inflammatory reaction of vascular endothelial cells. Puerarin (Pue), the main active component isolated from the rhizome of Pueraria lobata, is an isoflavone compound with potent antioxidant properties. Although Pue exhibits promising antiatherosclerotic pharmacological effects, only a few studies have reported its protective effect on endothelial cells. This study found that Pue could partly regulate mitochondrial function in human umbilical vein endothelial cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 65 publications
1
29
0
Order By: Relevance
“…Together, these studies suggested that inflammation and ROS-mediated oxidative stress could be one of the important reasons for ventricular remodeling in the later stages of CHD. Furthermore, Zhou et al (78) have demonstrated that LPS-induced inflammatory response and oxidative stress can injure HUVECs, leading to a decrease in the expression of SIRT-1 in endothelial cells and the dysfunction of mitochondrial energy metabolism and activation of the mitochondrial apoptotic pathways.…”
Section: Inflammation-induced Oxidative Stress In the Progress Of Myo...mentioning
confidence: 99%
See 1 more Smart Citation
“…Together, these studies suggested that inflammation and ROS-mediated oxidative stress could be one of the important reasons for ventricular remodeling in the later stages of CHD. Furthermore, Zhou et al (78) have demonstrated that LPS-induced inflammatory response and oxidative stress can injure HUVECs, leading to a decrease in the expression of SIRT-1 in endothelial cells and the dysfunction of mitochondrial energy metabolism and activation of the mitochondrial apoptotic pathways.…”
Section: Inflammation-induced Oxidative Stress In the Progress Of Myo...mentioning
confidence: 99%
“…PUE can improve mitochondrial energy metabolism by improving mitophagy or inhibiting LPS-induced inflammatory response in HUVECs, thereby regulating the mechanism of oxidative stress reduction balance. Moreover, the protective effect of PUE on HUVECs is closely related to the SIRT-1 signaling pathway (78).…”
Section: Pharmacological Intervention In Human Clinical Trialsmentioning
confidence: 99%
“…In recent years, the anti-inflammatory mechanisms of PR have been extensively studied, which involve the regulation of key signals such as TLR, Nrf2, HDAC and PPARα, [18][19][20][21][22] but also the improvement of organelle function. 23 However, no researches have yet explored whether PR reverses UUOmediated renal injury through anti-inflammatory and antifibrotic effects. In this context, we conceived the present study and hypothesised that PR could rescue renal function by regulating the NF-κB p65/STAT3 and TGF-β1/Smads pathways to inhibit renal fibrosis and inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Ohwi ( Zhang 2019 ). Puerarin exhibits a wide range of antioxidant activities in cardiovascular diseases, diabetes, obesity, osteoporosis, and other diseases ( Xu et al, 2021 ; Chang et al, 2021 ; Liu Y. et al, 2021 ; Xiao et al, 2020 ). In addition, puerarin has anti-inflammatory, anti-viral and other pharmacological activities ( Wang Z.-K. et al, 2020 ; Wang H. X. et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%